POLA PEMBINAAN KEMANDIRIAN SEBAGAI UPAYA MENGURANGI STRES PADA WARGA BINAAN DI LAPAS KELAS IIA BANYUWANGI - Sandi Diana Mardlatillah; M. Ali Makki (Sociocouns: Journal of Islamic Guidance and Counseling, 2021)
The prison environment is different from the environment in general because of the limited space for movement and the rules that must be obeyed. The limited space for movement does not rule out the possibility that the inmates feel stressed. Stress is a human psychophysical phenomenon where it is a physical and psychological response (reaction) that causes feelings of discomfort, uncomfortable, or easily pressured by the demands that are being faced. This study focuses on, 1) how is the pattern of self-reliance development for inmates in class IIA Banyuwangi prisons? 2) what are the benefits of self-reliance development as an effort to reduce stress on inmates in class IIA Banyuwangi prison? The method used in this study is a qualitative approach with a descriptive research model. Methods of data collection using interviews, documentation, and observation. The results of this study indicate that the application of the pattern of fostering independence by officers is by holding training, learning from friends and officers only as supervisors or facilitators. The benefits of fostering independence were as a provision to open a business independently for inmates, as a forum for re-honing their abilities during detention, and through fostering activities for independence inmates were able to manage the stress they felt by participating in programs provided according to their respective abilities.